Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
Đa thức có dạng \(x^{3a+1}+x^{3b+2}+1\) thì đưa về dạng \(\left(x^2+x+1\right)\cdot P\left(x\right)\) bạn nhé!
Bài làm:
\(x^5+x+1\)
\(=\left(x^5-x^2\right)+\left(x^2+x+1\right)\)
\(=x^2\left(x^3-1^3\right)+\left(x^2+x+1\right)\)
\(=x^2\left(x-1\right)\left(x^2+x+1\right)+\left(x^2+x+1\right)\)
\(=\left(x^2+x+1\right)\left(x^3-x^2+1\right)\)
\(x^5+x+1=x^5-x^2+x^2+x+1\)
\(=x^2\left(x^3-1\right)+x^2+x+1\)
\(=x^2\left(x-1\right)\left(x^2+x+1\right)+\left(x^2+x+1\right)\)
\(=\left(x^2+x+1\right)\left(x^2\left(x-1\right)+1\right)\)
a. 3x2– 7x + 2 = 3x2 – 6x – x + 2
= 3x(x -2) – (x - 2)
= (x - 2)(3x - 1)
b. a(x2 + 1) – x(a2 + 1) = ax2 + a – a2x – x
= ax(x - a) – (x - a)
= (x - a)(ax - 1)
a) \(3x^2-7x+2=3x^2-x-6x+2=x\left(3x-1\right)-2\left(3x-1\right)=\left(3x-1\right)\left(x-2\right)\)
b) \(a\left(x^2+1\right)-x\left(a^2+1\right)=\left(a^2+1\right)\left(a-x\right)\)
x5 + x4 + 1 = x5 - x3 - x2 - x4 + x2 + x + x3 - x - 1
= x2 ( x3 - x - 1 ) - x ( x3 - x - 1 ) + 1 ( x3 - x - 1 )
= ( x3 - x - 1 ) ( x2 - x + 1 )
x8 + x +1= x8 +x7 - x7 + x6 - x6 + x5 - x5 + x4 -x4 +x3 -x3 + x2 -x2 +x +1
= (x2+x+1)*(x6 -x5+x3-x2+1)
\(x^4+x^3+x^2-1\)
\(=x^3\left(x+1\right)+\left(x+1\right)\left(x-1\right)\)
\(=\left(x+1\right)\left(x^3+\left(x-1\right)\right)\)
Ủng hộ nha ^ _ ^
\(x^4+x^3+x^2-1\)
\(=x^2\left(x^2-1\right)+x^2-1\)
\(=\left(x^2+1\right)\left(x^2-1\right)\)
\(x^{12}-3x^6+1=\left(x^{12}+x^9-x^6\right)-\left(x^9-x^3+x^6\right)-\left(x^3-1+x^6\right)=x^6\left(x^6+x^3-1\right)-x^3\left(x^6+x^3-1\right)-\left(x^6+x^3-1\right)\)
\(=\left(x^6+x^3-1\right)\left(x^6-x^3-1\right)\)
`x^5 + x + 1 `
`= x^5 - x^4 + x^4 - x^3 + x^3 - x^2 + x^2 + x + 1`
`= x^4 (x-1) + x^3 (x-1) + x^2 (x-1) + x^2 + x + 1`
`= (x^4 + x^3 + x^2) (x - 1) + x^2 + x + 1`
`= x^2 . (x^2 + x + 1) (x - 1) + (x^2 + x + 1) `
`= (x^3 - x^2 + 1)(x^2 + x + 1) `